ANALISIS PATROLI PERINTIS PRESISI POLRES METRO TANGERANG KOTA MENGGUNAKAN BROKEN WINDOW THEORY - Anugrah, Bondan (Jurnal Ilmu Kepolisian, 2023)
The function of the police as one of the functions of the state government is in the field of maintaining security and securing the community, law enforcement, protector, protection and service to the community. In carrying out its function of eradicating disorders of deviance and crime, the motivations behind these crimes have been explored. Structural social conditions are not always the only trigger of criminal acts, where the circumstances and physical condition of the environment or infrastructure become a strong stimulus for crime and irregularities. Physical damage to an environment gives offenders the perception that the area is prone to crime and that people are so frightened that they will do nothing to stop the crime. This paper aims to explain the process of preventing and maintaining public safety and security in the jurisdiction of the Tangerang City Metro Police carried out by the Perintis Presisi Patrol team. This study uses the theory of broken windows as support analysis. This writing uses a qualitative descriptive approach. The data sources used are primary data,Â  as field observations and interviews and the secondary data as literature studies in the form of books, journals, and the results of previous studies with conclusions drawn. The results of the study show that based on the broken window theory, the decrease in the crime rate contained in the report chart of the Tangerang City Metro Police is the result of good cooperation carried out between the police institution and the community for concern for all forms of community security, regardless of the size of the disturbance or criminal act, even in micro level. The broken windows theory offers a clear, plausible and compelling perspective for police and the public to understand how best to deal with the increasing levels of crime and disorder in their areas.